2015
DOI: 10.1021/acs.nanolett.5b01429
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Charge Carrier Trapping in Quantum Dot Field Effect Transistors

Abstract: Noncrystalline semiconductor materials often exhibit hysteresis in charge transport measurements whose mechanism is largely unknown. Here we study the dynamics of charge injection and transport in PbS quantum dot (QD) monolayers in a field effect transistor (FET). Using Kelvin probe force microscopy, we measured the temporal response of the QDs as the channel material in a FET following step function changes of gate bias. The measurements reveal an exponential decay of mobile carrier density with time constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 29 publications
3
37
0
1
Order By: Relevance
“…The observation of two distinct distributions may explain why some groups reported states close to the valence level and others associated them with the conduction level. [9][10][11][12][13][14]28] The surface chemistry of PbS CQDs is more complex than simple schemes such as the one in Figure 1a suggest. Even assynthesized CQDs do not only exhibit two differently polarized crystal facets ((001) and (111)), but are also covered with hydroxyl and oleate ions additional to oleic acid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation of two distinct distributions may explain why some groups reported states close to the valence level and others associated them with the conduction level. [9][10][11][12][13][14]28] The surface chemistry of PbS CQDs is more complex than simple schemes such as the one in Figure 1a suggest. Even assynthesized CQDs do not only exhibit two differently polarized crystal facets ((001) and (111)), but are also covered with hydroxyl and oleate ions additional to oleic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Such defect states were observed for PbS before by various techniques. Reported were especially a state 0.2 eV above the valence level of 1,2-ethanedithiol or 1,3-mercaptopropionic acid (EDT, MPA) capped CQDs via Kelvin probe force microscopy (KPFM) and scanning tunneling spectroscopy (STS), [9][10][11][12] Additionally, a quasimetallic midgap band ≈0.4 eV below the conduction …”
mentioning
confidence: 99%
“…12 Remarkably, this is in good agreement with our previous work, where we found a band of IGS ≈ 0.2 eV above the valence band of PbS QDs, which form percolation pathways assisting carrier transport. 13,14 In addition, Sargent et al and Klimov et al found similar IGS using transient absorption and scanning tunneling spectroscopy (STS) methods. 7,8,15 Although the existence and the energy level of IGS have been established, until now the nature of the IGS is still unclear.…”
mentioning
confidence: 92%
“…[127][128][129] Um FET apresenta duas interfaces do filme fino de QD semicondutor que afetam substancialmente o desempenho do dispositivo: com a camada dielétrica colocada entre o eletrodo de porta (gate); com os eletrodos de fonte (source) e de dreno (drain). A Figura 6(A) ilustra um dispositivo FET com QD como camada semicondutora na arquitetura bottom-gate, bottom-contact, na qual o eletrodo porta está na base do transistor recoberto com a camada dielétrica e os eletrodos fonte e dreno depositados sobre a camada dielétrica.…”
Section: Transistores De Efeito De Campo -Fetsunclassified